THE PRIORITY OF THE MILITARY SERVICE IS TO ENSURE THE UNITY OF THE NATION AND SECURITY - Kamilov Feruz Bakhriddinovich (American Journals Publishing, 2023)
This article summarizes the most important importance of military service in guaranteeing the solidarity and security of a nation. Military service plays an important role in maintaining a cohesive society, protecting the nation from both internal and external threats. The main focus of this article is to emphasize how the military service is important by uniting the civilian unit under the common reason for the protection of their homeland. In addition, it is emphasized how to ensure the security of the nation through the tolerance and dedication of military personnel who work tirelessly to guard the borders and maintain peace within the country. In this annotation, its necessary role in maintaining the unity and security of the nation is covered by recognizing the importance of military service as the most fundamental task.
Keywords: National security, Declaration of Independence, Constitution, sovereignty, defense doctrine, normative document, territorial integrity, Supreme Assembly, foreign policy.